DRIVING SUSTAINABILITY THROUGH INNOVATION AND ENVIRONMENTAL BEHAVIOR: THE ROLE OF TRANSFORMATIONAL LEADERSHIP - Hani Fadila; Eko Nur Fu’ad (Jurnal Ilmu Manajemen (JIMMU), 2025)
This study investigates the relationship between transformational leadership and sustainable performance through two mediating variables: innovative work behavior and pro-environmental behavior. A total of 210 employees from CV Kalingga Keling Jati were surveyed using a Likert scale (1–5) questionnaire with a quantitative approach. The data were analyzed using SmartPLS. The findings reveal that transformational leadership has a positive and significant effect on pro-environmental behavior, innovative work behavior, and sustainable performance. Furthermore, the effect of transformational leadership on sustainable performance is mediated by both innovative and environmentally friendly work behaviors. This emphasizes the role of transformational leaders in fostering a workplace culture that encourages creativity and environmental responsibility, which in turn enhances business sustainability. Practically, this suggests the need for leadership development programs that emphasize creativity and environmental awareness.